Science and Non-Science Majors’ Mental Models of Nuclear Power: Does the Program of Study Matter? - Es, Hüseyin; Yenilmez Türkoglu, Ayse (Acta Didactica Napocensia, 2021)
The purpose of this study was to characterize science and non-science majors’ mental models of nuclear power plants through their drawings. For this purpose, a total of 27 Theology and 26 Science Education college students were participated in the study. To collect data, students were first asked to state their decisions about the construction of nuclear power plant in the city they live, and then to think about nuclear power plants in their minds and draw the revived images on a paper. Data were analyzed through content analysis based on the SEE-STEP model. Findings revealed that religious beliefs and/or education may affect college students’ reactions to nuclear power plants. That is, while most theology majors approached the construction of nuclear power plants positively, majority of science education majors did not. Theology majors referred mostly to economy in their drawings, while science education majors mostly to environment. Regardless of the program of study, on the other hand, the codes emerged from the drawings were mostly about environment, which was followed by technology, economics and science. Ethics was the least common subject area referred in the drawings of the students from both programs of study."